Noncommutative Multi-Solitons in a Modified Chiral Model in 2+1 Dimensions (Communications in Mathematical Research, 2021)
Multi-soliton configurations of a Moyal-type noncommutative deformedmodified 2+1 chiral model have been constructed by dressing method several yearsago. These configurations have no-scattering property. By making a second-orderpole in the dressing ansatz, two-soliton configurations with genuine soliton-solitoninteraction were constructed after that. We go on in this paper to construct a largefamily of multi-soliton configurations with scattering property by using the noncommutative extension of Bäcklund transformations defined by Dai and Terng in a recentpaper.